Toward healthier futures in post‐pandemic times: Political ecology, racial capitalism, and black feminist approaches to care. Issue 2 (4th January 2022) - Neely, Abigail H.; Lopez, Patricia J.
Abstract: The COVID‐19 pandemic and state violence converged in the U.S. in 2020 highlighting the uneven distribution of illness and death. In this article, we mobilize three bodies of literature–political ecologies of health and the body, Black geographies and racial capitalism, and Black feminist work on care—to understand the disproportionate impacts of the COVID‐19 pandemic on Black, Brown, Indigenous, and Asian people, and to imagine different, more just futures. We argue that these literatures center relationships, enabling an analysis that incorporates viruses and cellular processes, histories of racism, power differences, and political economy. We conclude by taking inspiration from the uprisings and Black feminism to envision a more caring future that nurtures relationships.